Study of renal function during acute phase and recovery in patients with COVID – 19 in Baghdad/Iraq (Journal of Pharmaceutical Negative Results, 2022)
This study aims to investigate traces of COVID – 19 on renal system during infection & after recovery in city of Baghdad from October 2021 till April 2022.Method: Patients were consisted of 120 individuals with acute then to convalescent phase of COVID-19 and 60 healthy controls, all aged between 19 & 61 years.They were consisted of equal halves of males & females, for both patients & controls.Tests that were depended in this study are: Blood urea, serum creatinine & serum uric acid; all samples are of serum; that had been done using Roche – Integra 400 plus auto analyser at Al-Karkh Medical Laboratory in Baghdad.Result: Renal impairment & problems were of several dilemmas that raised highly with proceeding of COVID – 19, made dysfunction of kidneys & other correlated parts of renal system parts a very significant criterion among patients suffering this problem; especially if there was a familiar history in these organs; like renal stone formation, uricemia & recurrent urinary tract infection; making consequences of this disease the worst among other problems that can take effect on renal system; rather than chemical toxification & cancers. Blood urea had scored in males in acute & recovery phases of (38.08±15.36) & (43.27±18.13) respectively, while in females was(28.57±7.56) & (32.25±8.49) in same attribute, with high significance of (p<0.01 HS) in acute phase & (p>0.05 NS) for recovery phase.Serum creatinine levels were lower in females than of males in both phases; where scores at (0.6517±0.19) in acute phase & (0.81±0.19) after recovery; which means that they stayed in normal ranges; while in males level of creatinine scored (0.94±0.370) & (1.19±0.45) in cue; hitting the highest normal ranges & made males in higher risk for any renal proper functioning, with high significance of (p<0.01 HS) for both.Results of S. uric acid were slightly near the upper limits for females at (5.23±1.13) & (5.48±0.79) for acute & recovery phases in correspondence, while males crossed the borders of normal ranges in both phases; (6.31±1.17) & (7.07±1.09) respectively, (p<0.01 HS) for both.